The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s13300-019-00724-w
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Glucose Co-Transporter 2 Inhibitors and Fracture Risk

Abstract: Patients with type 2 diabetes mellitus (T2DM) appear to have increased risk for fractures. In this context, the finding that canagliflozin, a sodiumglucose co-transporter-2 (SGLT) inhibitor, increased the risk for fracture compared with placebo in the Canagliflozin Cardiovascular Assessment Study (CANVAS), a large randomized controlled trial (RCT) in patients with established cardiovascular disease or multiple cardiovascular risk factors, created concern. In the present review, we summarize the data regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…This observation was consistent across all groups of eGFR, ranging from 30 to <90 ml per minute per 1.73 m 2 (Jardine et al, 2020). Intriguingly, the use of dapagliflozin and empagliflozin does not increase the incidence of fractures (Erythropoulou‐Kaltsidou et al, 2020) or amputations (Scheen, 2020) in patients. An expert panel overview concluded that an increased amputation risk in patients was related only to canagliflozin use (not with other SGTL2‐Is) and hence, not generalizable to SGLT2‐Is class (Katsiki et al, 2019).…”
Section: Adverse Effects Of Sglt2‐ismentioning
confidence: 99%
“…This observation was consistent across all groups of eGFR, ranging from 30 to <90 ml per minute per 1.73 m 2 (Jardine et al, 2020). Intriguingly, the use of dapagliflozin and empagliflozin does not increase the incidence of fractures (Erythropoulou‐Kaltsidou et al, 2020) or amputations (Scheen, 2020) in patients. An expert panel overview concluded that an increased amputation risk in patients was related only to canagliflozin use (not with other SGTL2‐Is) and hence, not generalizable to SGLT2‐Is class (Katsiki et al, 2019).…”
Section: Adverse Effects Of Sglt2‐ismentioning
confidence: 99%
“…FGF23 is known to be provoked by increased phosphate, and the latter also provokes PTH excretion. Therefore, by proxy, SGLT2i by increasing phosphate, increase both FGF23 and PTH[ 120 , 121 ]. Within this small study, FGF23 levels peaked roughly 12 h after phosphate reached its maximus, consistent with physiologic studies of FGF23 expression[ 122 ].…”
Section: Hyperphosphatemia Sglt2 and Cardiorenal Implicationsmentioning
confidence: 99%
“…FGF23 acts on the proximal tubule, inhibiting NPT2, a cotransporter of sodium and phosphate (which may further explain why natriuresis is not the predominant mechanism of urinary loss within SGLT2i administration after phosphate levels subsequently reach clinically relevant concentrations)[ 123 ]. Interestingly, FGF23 suppresses 1-α-hydroxylation of Vitamin D to activate it , while PTH promotes 1-α-hydroxylation resulting in a mismatch of calcium reabsorption[ 121 ]. The dynamics of this small-scale Canagliflozin study that measured FGF23, PTH, and 1,25-dihydroxyvitamin D levels on a daily basis implied that early FGF23 expression resulted in a transient hypocalcemia.…”
Section: Hyperphosphatemia Sglt2 and Cardiorenal Implicationsmentioning
confidence: 99%
“…Canagliflozin and ertugliflozin have demonstrated increased risk of lower limb amputations, whereas bone fracture risk has been specifically observed with canagliflozin in the clinically indicated range of eGFR [66,67]. Several plausible mechanisms for these adverse reactions have been proposed, and are reviewed elsewhere [68,69]. The CRE-DENCE study was designed with specific measures to minimize the risk of lower limb amputations; this study did not demonstrate significantly increased risk of lower limb amputations with canagliflozin [5].…”
Section: Pharmacovigilancementioning
confidence: 99%